2013
DOI: 10.1080/14786419.2013.838241
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and biological activities from roots ofEnkleia siamensis

Abstract: Chemical investigation from roots of Enkleia siamensis (Kurz) Nervling resulted in the isolation of 10 compounds. Their structures were established on the basis of 1D and 2D NMR spectroscopic data as linobiflavonoid (1), chamaejasmin (2), 7-O-β-D-glucopyranosylchamaejasmin (3), ormocarpin (4), (-)-wikstromol (5), matairesinol (6), (+)-lariciresinol (7), umbelliferone (8), daphnoretin (9) and carthamidin (10). Compounds 2 and 8 showed cytotoxicity against KB, MCF-7 and NCI-H187 cancer cell lines. Compounds 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, it is urgent to find novel and effective candidates to enhance the therapeutic effect of breast cancer. Daphnoretin has been shown to exert antitumor activity to colon cancer HCT116 cells, cervical cancer HeLa cells, oral epidermoid carcinoma KB cells, lung cancer A549 cells, and NCI-H187 cells. , In this study, we found that daphnoretin could remarkably suppress breast cancer cell proliferation through arresting the cell cycle and inducing cell apoptosis, which is related to the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, it is urgent to find novel and effective candidates to enhance the therapeutic effect of breast cancer. Daphnoretin has been shown to exert antitumor activity to colon cancer HCT116 cells, cervical cancer HeLa cells, oral epidermoid carcinoma KB cells, lung cancer A549 cells, and NCI-H187 cells. , In this study, we found that daphnoretin could remarkably suppress breast cancer cell proliferation through arresting the cell cycle and inducing cell apoptosis, which is related to the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 72%
“…Further studies demonstrated that daphnoretin remarkably induced apoptosis through a mitochondria-dependent apoptotic pathway . Furthermore, several studies have revealed that daphnoretin showed powerful cytotoxicity to lung cancer A549 cells, NCI-H187 cells, and oral epidermoid carcinoma KB cells. , However, the therapeutic effect of daphnoretin in breast cancer has still not been completely studied.…”
Section: Introductionmentioning
confidence: 99%